THE IMPACT OF MINIMAL INVASIVE SURGERY COURSE AND THE BARRIERS FACED BY GENERAL SURGEON IN ITS IMPLEMENTATION - Ishaqi, Habibullah; Abbasi, Sahar Zubair (Pakistan Armed Forces Medical Journal, 2019)
Objective:To assess the impact of Minimal Invasive Surgery (MIS) course for Surgeons of Quetta and to identify the barriers to adoption of MIS in Quetta.Study Design: Cross sectional descriptive study.Place and Duration of Study: Sheikh Khalifa Bin Zayyed Medical Complex, Quetta, from Jan to Jul 2017.Methodology:Surgeons of Quetta who attended Minimal Invasive Surgery course were included in the study. After 6 months of the course, data was collected from the surgeons. The questionnaire had closely ended self-administered questionnaire having 15 questions regarding use of MIS in practice and possible barriers to non-implementation. Data was analyzed by using IBM SPSS Statistics version 20. Frequency and percentages were calculated for the categorical variables.Results:Questionnaire was sent to 43 participants, 37 completed the proforma. Response rate was 86%. There were 31 male (83.8%) and 6 (16.2%) female. There were 31 male (83.8%) and 6 (16.2%) female out of 43 Surgeons. The majority of the fellow surgeons were from year 2001-2005 (37.8%). About 59.5% of the surgeons belonged to academic. The focus of the practice of majority of the surgeons was general (97.3%). Ninety four point six percent of the Surgeons who attended the course had improved the understanding and skills of MIS. Only 51.4% cholecystectomy, 21.6% appendectomy and 16.2% oophorectomy of the Surgeons were able to perform Minimal Invasive Surgery in Quetta. The most common barrier for not performing Minimal Invasive Surgery in Quetta were lack of resources and lack of trained nursing staff 94.5%.Conclusion:The.........